2014
DOI: 10.1097/gox.0000000000000064
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Lower Limb Lymphedema Animal Model with Combined Lymphadenectomy and Low-dose Radiation

Abstract: Background:This study was aimed to establish a consistent lower limb lymphedema animal model for further investigation of the mechanism and treatment of lymphedema.Methods:Lymphedema in the lower extremity was created by removing unilateral inguinal lymph nodes followed by 20, 30, and 40 Gy (groups IA, IB, and IC, respectively) radiation or by removing both inguinal lymph nodes and popliteal lymph nodes followed by 20 Gy (group II) radiation in Sprague-Dawley rats (350–400 g). Tc99 lymphoscintigraphy was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 20 publications
3
57
1
Order By: Relevance
“…27 However, recent attempts to combine surgery with pre-or postoperative radiation in the hind limb of rodents, has led to improved models that better recapitulate human disease. 21,28 In this study, we wished to establish a surgically induced hind limb lymphedema model that had a high incidence of disease that could be easily measured over time. To accomplish this, we preirradiated the hind limb and subsequently performed popliteal lymphadenectomy, deep lymphatic vessel ablation, and complete disruption of dermal lymphatics via a circumferential skin incision.…”
Section: Discussionmentioning
confidence: 99%
“…27 However, recent attempts to combine surgery with pre-or postoperative radiation in the hind limb of rodents, has led to improved models that better recapitulate human disease. 21,28 In this study, we wished to establish a surgically induced hind limb lymphedema model that had a high incidence of disease that could be easily measured over time. To accomplish this, we preirradiated the hind limb and subsequently performed popliteal lymphadenectomy, deep lymphatic vessel ablation, and complete disruption of dermal lymphatics via a circumferential skin incision.…”
Section: Discussionmentioning
confidence: 99%
“…Increased adiponectin expression, which correlates with fat accumulation caused by lymph stasis, was also observed in mouse tail surgical model of lymphedema (Aschen et al, 2012) (Table 1). Moreover, IL-6 expression which correlates with adipose tissue depots in obese patients (Mohamed-Ali et al, 1997;Fried et al, 1998) Knight et al, 1987;Blum et al, 2010;Lahteenvuo et al, 2011;Cuzzone et al, 2014;Wu et al, 2014;Yang et al, 2014;Triacca et al, 2019;Wang et al, 2020 Mouse Rat Gardenier et al, 2016 has also been shown to be increased in human and mouse lymphedematous tissues as well as in serum of lymphedema patients (Olszewski et al, 1992;Cuzzone et al, 2014). Increased IL-6 expression in lymphedematous murine tissues is associated with fat deposition, and it is postulated that its role is to regulate adipose tissue homeostasis since blocking its activity limits the expansion of adipose tissue .…”
Section: Adipose Tissue Expansion and Remodeling In Lymphedemamentioning
confidence: 99%
“…Although a variety of models that display some characteristics of clinical lymphedema have been developed, these models have significant limitations, including high morbidity and spontaneous resolution of swelling (8)(9)(10). The necessity for extensive surgical manipulation (i.e., full-thickness excision of large portions of skin) in most models has made it difficult to separate wound healing from lymphatic regeneration and does not accurately model human pathology, in which only lymph nodes are removed.…”
Section: Introductionmentioning
confidence: 99%